2017
DOI: 10.1109/tim.2017.2728398
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Approach for Distribution System State Estimation With Non-Gaussian Uncertainty Models

Abstract: To deal with the increasing complexity of distribution networks that are experiencing important changes, due to the widespread installation of distributed generation and the expected penetration of new energy resources, modern control applications must rely on an accurate picture of the grid status, given by the distribution system state estimation (DSSE). The DSSE is required to integrate all the available information on loads and generators power exchanges (pseudomeasurements) with the real-time measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…SM measurements can be helpful also to build pseudo-measurements; this is not a simple task because it involves load and generation forecasting (as in [75], see the discussion in the next section), data modeling and, even though it is often neglected, uncertainty evaluation. Pseudo-measurements are built by means of statistical analysis, AI, and cluster analysis methods [71,76,77], while ad-hoc techniques must be designed to include complex non-Gaussian models in DSSE algorithms [78].…”
Section: Distribution System State Estimationmentioning
confidence: 99%
“…SM measurements can be helpful also to build pseudo-measurements; this is not a simple task because it involves load and generation forecasting (as in [75], see the discussion in the next section), data modeling and, even though it is often neglected, uncertainty evaluation. Pseudo-measurements are built by means of statistical analysis, AI, and cluster analysis methods [71,76,77], while ad-hoc techniques must be designed to include complex non-Gaussian models in DSSE algorithms [78].…”
Section: Distribution System State Estimationmentioning
confidence: 99%
“…The establishment and analysis of the whole model are based on the Bayesian probability theorem [13] as shown in Equation (1):Pfalse(A|Bfalse)=Pfalse(B|Afalse)Pfalse(Afalse)/Pfalse(Bfalse),Pfalse(A|Bfalse)Pfalse(B|Afalse)Pfalse(Afalse) where A represents the normal posture of the tester, and B represents the triangle area composed of three barycenters.…”
Section: Methodsmentioning
confidence: 99%
“…Using Mean Squared Estimator (MSE) an analytic SE formulation is obtained in [29] which does not depend on Gaussian uncertainty assumptions and is capable of bad data measurement detection. A similar estimator is used in [30], where a Bayesian alternative to WLS is proposed. It is shown that the Bayesian approach has specifically better performance in presence of non-Gaussian uncertainty.…”
Section: Fundamentals Of Sementioning
confidence: 99%